2010
DOI: 10.1590/s1808-86942010000100011
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do Voice Handicap Index em pacientes com perda auditiva neurossensorial bilateral a partir de grau moderado

Abstract: Voi ce and speech are regulated by hearing. Vocal disorders in patients with hearing loss have not been evaluated yet as to the subjective degree of disability they cause in this group. Aim: to compare the results of the Voice Handicap Index (VHI) obtained for patients with normal hearing and moderate to profound bilateral sensorineural hearing loss. Study design: Controlled, cross-sectional. Materials and Methods: A total of 76 adult patients being treated on a University Otolaryngology center were enrolled (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Thus, it appears that the emotional impact was greater in males, so that results in the two protocols were similar. This finding agrees with two studies that compared gender with VHI protocol and did not observed significant differences 19,20 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, it appears that the emotional impact was greater in males, so that results in the two protocols were similar. This finding agrees with two studies that compared gender with VHI protocol and did not observed significant differences 19,20 .…”
Section: Discussionsupporting
confidence: 93%
“…According to the literature, the age variable deserves attention, because as age advance, the vocal efficiency decreases, with greater or lesser vocal impact 13 , and a positive correlation was found between the total score of VHI and age 19 . Other studies have also found that elderly showed lower scores of V-RQOL compared to younger individuals, realizing greater impact of dysphony on their quality of life 23,24 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil most part of researches performed with the questionnaires quoted above has focus in the self-assessment specific group results, as for voice professionals' category or diverse pathology carriers [11][12][13][14][15] . In some cases, the data collection meet the subjects, which not necessarily have a voice disturb and/or sought for speech language pathology help 11,12 .…”
mentioning
confidence: 99%
“…In some cases, the data collection meet the subjects, which not necessarily have a voice disturb and/or sought for speech language pathology help 11,12 .…”
mentioning
confidence: 99%